Water scarcity variations within a country: a case study of Sri Lanka - Amarasinghe, Upali A.; Mutuwatte, L.P.; Sakthivadivel, Ramaswamy (International Water Management Institute, 1999)
Sri Lanka is a country with vast spatial and seasonal variations of water supply and demand. Statistics in the form of aggregated information at national level sometimes mask issues of local water scarcity. But when the same indicators are used at subunit level, a substantial area of the country comes under severe water-scarce conditions. Knowledge of subunit level water scarcities is very important because most of the food requirement of the country at present comes from water-scarce regions and projected additional requirements are also to be met by the same regions.